Women’s Social Participation Based on Motahhari’s Approach to Natural Rights - Sareh Larijani (پژوهشنامه فلسفه دین, 2022)
Today, in spite of all the Muslim intellectuals’ efforts with regard to women’s socio-political participation, there are still doubts about this issue in some Muslim countries. Even in Iranian society, the status of women in certain social matters is still not clear. In this article, we are going to investigate the issue from a religious perspective in the light of Morteza Motahhari’s intellectual arguments based on the concepts of social justice and natural rights (Huquq-i fitri). In fact, women’s social participation is still one of the controversial issues among Muslim thinkers. Hence, we are witnessing two extremist tendencies in this area. On the one hand, there are traditionalists who restrict women’s social participation because of an unjustified connection between women’s social activity and the increase in sensuality. On the other hand, there are those who, influenced by Western liberalism and so emphasizing freedom and equality, expect women’s maximum public activities even though they do not present any clear structure for women’s public life. These intellectuals either do not make their arguments based on any religious notions or theorize their approach based on a weak religious argument. This study aims to present an alternative approach that avoids extremism and is based on the principles of justice and natural rights. This alternative approach according to Motahhari’s thought has three main components: 1. Men and women are equal in humanity, 2. Both genders possess capacities and potentialities on which the happiness of human are dependent, 3. To actualize some of these potentialities, humans need to participate in social activities. This study is a library research project based on textual analysis.